A Histological Study of Aspergillus flavus Colonization of Wound Inoculated Maize Kernels of Resistant and Susceptible Maize Hybrids in the Field - Windham, Gary L.; Williams, William P.; Mylroie, J. E.; Reid, Cedric X.; Womack, Erika D. (Frontiers in Microbiology, 2018)
Aspergillus flavus colonization in developing kernels of maize single-cross hybrids resistant (Mp313E × Mp717) and susceptible (GA209 × T173) to aflatoxin accumulation was determined in the field over three growing seasons (2012–2014). Plants were hand pollinated, and individual kernels were inoculated with a needle dipped in a suspension of A. flavus conidia 21 days after pollination. Kernels were harvested at 1- to 2-day intervals from 1 to 21 days after inoculation (DAI). Kernels were placed in FAA fixative, dehydrated, embedded in paraffin, sectioned, and stained with toluidine blue. Kernels were also collected additional kernels for aflatoxin analyses in 2013 and 2014. At 2 DAI, A. flavus hyphae were observed among endosperm cells in the susceptible hybrid, but colonization of the endosperm in the resistant hybrid was limited to the wound site of the resistant hybrid. Sections of the scutellum of the susceptible hybrid were colonized by A. flavus by 5 DAI. Fungal growth was slower in the resistant hybrid compared to the susceptible hybrid. By 10 DAI, A. flavus had colonized a large section of the embryo in the susceptible hybrid; whereas in the resistant hybrid, approximately half of the endosperm had been colonized and very few cells in the embryo were colonized. Fungal colonization in some of the kernels of the resistant hybrid was slowed in the aleurone layer or at the endosperm-scutellum interface. In wounded kernels with intact aleurone layers, the fungus spread around the kernel between the pericarp and aleurone layer with minimal colonization of the endosperm. Aflatoxin B1 was first detected in susceptible kernel tissues 8 DAI in 2013 (14 μg/kg) and 2014 (18 μg/kg). The resistant hybrid had significantly lower levels of aflatoxin accumulation compared to the susceptible hybrid at harvests 10, 21, and 28 DAI in 2013, and 20 and 24 DAI in 2014. Our study found differential A. flavus colonization of susceptible and resistant kernel tissues, and that the aleurone and the outer layer of the scutellum slowed the rate of colonization by A. flavus.